Abortion In The Aspects of Criminal Law And Health - Agung Putri Harsha Satya Nugraha; Vivin Indrianita; Bastianto Nugroho (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
Abortion or commonly referred to abortion into the human civilization because humans do not want the pregnancy. Since centuries ago, many nations have known checkers wear some plant species believed to stimulate contraction of uterus to shed or dropped fetus. Abortion itself can occur either due to human actions (abortion provocatus) or because of natural causes, that happens by it self, in the sense that not because of human actions (abortion spontatus). Abortion is happening because of human actions can occur either because it is driven by medical reasons, such as pregnant women who suffer from a disease and to save the lives of these women then abortion must be terminated (abortion therapeuticus). Besides, for reasons that are not justified by the law (abortion criminalis). The method used in this research is normative juridical consideration that the starting point of the research analysis of the laws and regulations of the Criminal Code, Act No. 35 of 2014 on the Amendment of Act No. 23 of 2002 on Child Protection, and Law No. 36 of 2009 on health associated with the renewal of the crime of abortion.